The effect of overload on the fatigue crack growth behaviour of 304 stainless steel in hydrogen - Kelestemur, MH; Chaki, TK (Blackwell Science Ltd, 2001)
Fatigue crack growth (FCG) behaviour and its characteristics following tensile overloads were investigated for AISI 304 stainless steel in three different atmospheres; namely dry argon, moist air and hydrogen. The FCG tests were performed by MTS 810 serohydraulic machine. CT specimens were used for the tests and crack closure measurements were made using an extensometer. FCG rates of 304 stainless steel at both dry argon and moist air atmospheres have shown almost the same behaviour. In other words, the effect of moisture on FCG of this material is very small. However, in a hydrogen atmosphere, the material showed considerably higher crack growth rate in all regimes. In general, for all environments, the initial effect of overloads was to accelerate the FCG rate for a short distance (less than a mm) after which retardation occurred for a considerable amount of time. The main causes for retardation were found as crack blunting and a long reinitiation period for the fatigue crack. Regarding the environmental effect, the overload retardation was lowest in a hydrogen atmosphere. This low degree of retardation was explained by a hydrogen embrittlement mechanism. In a general sense, hydrogen may cause a different crack closure mechanism and hydrogen induced crack closure has come in to the picture. Scanning electron microscope and light microscope examinations agreed well with the above results.
Keywords: fatigue crack growth; 304 stainless steel; hydrogen induced crack closure and overload